(untitled) (Research, Society and Development, 2019)
The aim of this study was to describe, in a systematic review, the results of studies that investigated a possible relationship between serum vitamin D levels in the elderly, alzheimer’s disease and cognitive dysfunction in these. The bibliographic survey was performed in the Pubmed, Scielo and Science Direct databases. The keywords used were: "vitamin d", "hypovitaminosis d", "cognitive dysfunction", "disease alzheimer" and "alzheimer". The systematic review protocol followed the recommendations of the Joanna Briggs Institute Reviewer Manual. Twelve studies were used to compose this review. Clinical trials were conducted with individuals of both sexes, aged over 65 years, in 8 different countries. All selected studies evaluated vitamin D deficiency by serum 25-hydroxyvitamin D (25 (OH) D) concentrations and performed a cognitive function assessment test in the elderly. It can be observed that elderly with Alzheimer’s disease or cognitive impairment had lower 25 (OH) D concentrations compared to normal, and the scores of cognitive assessment methods were lower in individuals with lower 25 (OH) D concentrations.